Imaging anatomy. Volume 2, Abdomen and pelvis : text and atlas - Saremi, Farhood; Sánchez-Quintana, Damián (New York : Thieme, 2023)
"Normal imaging anatomy and variants, including diagnostic and surgical anatomy, are the cornerstones of radiologic knowledge. Imaging Anatomy: Text and Atlas Volume 2, Abdomen and Pelvis is the second in a series of four richly illustrated radiologic references edited by distinguished radiologist Farhood Saremi. The atlas is coedited by esteemed colleagues Damián Sánchez-Quintana, Hiro Kiyosue, Dakshesh B. Patel, Meng Law, and R. Shane Tubbs with contributions from an impressive cadre of international authors. Succinctly written text and superb images provide readers with a virtual, user-friendly dissection experience"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 29, 2024).
eBooks on EBSCOhost
Keywords: Diagnostic imaging -- Atlases; Abdomen -- Anatomy -- Atlases; Pelvis -- Anatomy -- Atlases; Abdomen -- anatomy & histology; Abdomen -- diagnostic imaging; Pelvis -- anatomy & histology; Pelvis -- diagnostic imaging; Diagnostic Imaging -- methods; Imagerie pour le diagnostic -- Atlas; Abdomen -- Anatomie -- Atlas; Bassin (Anatomie) -- Anatomie -- Atlas; MEDICAL / Radiology, Radiotherapy & Nuclear Medicine; MEDICAL / Gastroenterology; Abdomen; Diagnostic imaging; Pelvis; Atlas; atlases; Anatomical atlases; Atlases; Scientific atlases; Atlases; Atlas